DD-012 Pharmacists and biosimilars: when "strong" actions means "strong" outcomes. (24th February 2014) - Uomo, I; Pastorello, M
Abstract : Background: Despite new documents published from EMA and the Italian Drug Agency with the aim of clarifying the quality assurance, efficacy and safety of biosimilar drugs, the clinicians are still reluctant to use them. In particular, biosimilar erythropoietins (ESA) and G-CSF growth factors have been shown to be value for money and to have the same therapeutic effects as the originators. However, from the data provided from the database of the Department of Pharmacy (DP) of Palermo (1, 200, 000 inhabitants) collecting prescriptions from 5 public hospitals, 1 university hospital and 20 dialysis centres, the percentage of biosimilars prescribed during 2012 was only 2.5% on the total of ESAs (alpha, beta, nesp, cera) and 3.2% of the total of G-CSF (filgrastim, lenograstim, pegfilgrastim). Purpose: To evaluate the outcomes of pharmacist involvement in the promotion of biosimilars. Materials and methods: The DP began a new strategy to increase the use of biosimilars: in February 2013, the DP informed all the clinicians that in all treatment-naïve patients the pharmacists were authorised to automatically substitute the brand with a biosimilar. The clinicians were allowed to prevent this from completing a brief reasoned opinion attached to the prescription. As the result, the Commission on Therapeutic Formulary of the Sicilian Health Structures stated, at the end of March, that all the patients starting treatment must be started with a biosimilar. Results: In the first nine months of 2013 the percentages grew from 2.5% to 19% for ESAs and from 3.2% to 26.1% for G-CSF. The total savings were 2, 694, 578 euros for both classes compared with 2012. In terms of safety, only one patient showed a mild adverse drug reaction (headache, as mentioned in the expected side effects). In terms of efficacy, we received three reports of non-responding patients. The inefficacy of the administered drugs was based on the Hb value, which remained stable and lower than the standard value after two months. Conclusions: This initiative was very difficult because the clinicians the claim the right to choose the treatment, but all the previous weak actions (courses, leaflets, publicity of the EMA regulations) did not work in the past and Sicily was one of the worst regions in terms of use of biosimilars. We now observe that many clinicians, especially the oncologists, are changing their minds, helping us to achieve large savings and in the meanwhile respecting the patient's safety. No conflict of interest.